Macrolide-resistant Mycoplasma genitalium in male and female patients attending a Northern Irish Genitourinary Medicine Clinic. Issue Volume 1(2019)Issue A (8th March 2019) - Cox, Ciara; McKenna, James; McCaughey, Conall; Watt, Alison
Abstract : Background: Mycoplasma genitalium (MG) can cause urethritis in men and pelvic inflammatory disease in women. Despite the increasing rate of MG resistance to first-line macrolide treatment due to 23S rRNA gene mutations, the availability of testing remains limited in UK laboratories. This study obtained preliminary data on the rate of macrolide resistant strains circulating in N. Ireland. Methods: Clinical specimens from 1052 patients attending a Genitourinary Medicine (GUM) clinic in Belfast from April 2017 to April 2018 were screened using an in-house MG PCR assay. MG positive samples were subsequently tested using Resistance Plus ™ MG assay (Speedx, Australia) to detect 23S rRNA gene mutations associated with macrolide resistance. Results: Amongst all study samples, 3.9 % ( n =41) tested positive for MG. Out of these 41.5 % ( n =17) had a 23S rRNA mutation. The rate of MG was highest in rectal swabs (8.13 %) followed by vaginal swabs (4.96 %) and then male urines (2.85 %). The rate of 23 S rRNA mutations associated with macrolide resistance in positive vaginal swabs was 21.4 % whereas the rate amongst urine and rectal swabs was at least 50 %. Conclusion: Data from this study adds to the evidence base to perform MG testing in risk groups in N. Ireland to improve patient outcomes and reduce antimicrobial resistance.